RADIKALISASI GERAKAN JAMAAH ANSHARUT TAUHID DAN PENGARUH ISIS DI INDONESIA - Asman Abdullah (Jurnal Sosiologi Reflektif, 2018)
This research was a case study that observed the movement of Jamaah Anshorut Tauhid. JAT movement is a jihad movement with the aim of fighting for Islamic Sharia in Indonesia. This research uses qualitative deskriptif method in direct contact with the object under study. It gives a complete picture of the phenomenon of radical Islamic JAT movements that was religiously motivated and understand the process of dynamics and the purpose of the social change that they want. The radical changes that they expect was contradict with the regime in Indonesia. The government's refreshing action accompanies every step of the JAT jihadists. In fact, excessive force often carried out by the authorities to provide a deterrent effect. But such actions only lead to jihadist heroism and reinforce their beliefs. Two things should be explained in the JAT movement, firstly, JAT involvement in Aceh military training in 2010. This military training involved cross-tanzhim jihad in Indonesia. The alumnus of this training will form a new radical network affiliated with ISIS. Second, the influence of ISIS in Indonesia caused a split in JAT. For JAT jihadi that supports ISIS still survives under the leadership of Abu Bakar Ba'asyir and Aman Abdurrahman while those who refuse to join ISIS have to get out of tanzhim. Those who came out of JAT formed a new organisation with the name of Jamaah Anshorut Syariah (JAS) under the leadership of Muhammad Achwan.Penelitian ini merupakan studi kasus yang menyorot gerakan Jamaah Anshorut Tauhid. Gerakan JAT merupakan gerakan jihad dengan tujuan memperjuangkan 214 Syariat Islam di Indonesia. Penelitian ini menggunakan metode deskriptik kualitatif yang bersentuhan langsung dengan obyek yang diteliti. Memberikan gambaran utuh fenomena gerakan radikal Islam JAT yang bermotif agama dan memahami proses dinamika dan tujuan dari perubahan sosial yang hendak mereka wujudkan. Perubahan radikal yang mereka harapkan bertentangan dengan rezim di Indonesia. Tindakan refresif pemerintah mengiringi setiap langkah para jihadis JAT. Bahkan kerapkali kekerasan berlebihan dilakukan aparat untuk memberikan efek jera. Tetapi tindakan seperti ini hanya menimbulkan sikap heroisme jihadis dan semakin meneguhkan keyakinan mereka. Dua hal yang patut disorot dari gerakan JAT pertama, keterlibatan JAT dalam pelatihan militer Aceh tahun 2010. Pelatihan militer ini melibatkan lintas tanzhim jihad di Indonesia. Alumni dari pelatihan ini kelak membentuk jaringan radikal baru yang berafiliasi dengan ISIS. Kedua, pengaruh ISIS di Indonesia melahirkan perpecahan bagi JAT. Bagi jihadi JAT yang mendukung ISIS tetap bertahan dibawah pimpinan Abu Bakar Ba’asyir dan Aman Abdurrahman sedangkan yang menolak bergabung dengan ISIS harus keluar dari tanzhim. Mereka yang keluar dari JAT membentuk jamaah baru dengan nama Jamaah Anshorut Syariah (JAS) dibawah pimpinan Muhammad Achwan.